Synthesis of lessons-learned in successful scale-out of Climate Smart Cocoa through the private sector in Ghana - Dalaa, Mustapha Alasan; Saeed, Abdul-Razak; Deffor, Eric Worlanyo; Kofituo, Rich Kofi; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
CCAFS II Cocoa project was initiated in 2019 to consolidate the gains of CCAFS I on Mainstreaming Climate Smart Cocoa Value Chains. The focus of CCAFS 1) Conduct a detailed cost-benefit analysis (CBA) of the CSC packages and augment that with return on investment on these practices to inform specific policies/actors on impact lending in cocoa; 2) Co-generate CBA data for CSC packages with the private sector on the stepwise approach to influence a sector-wide policy strategy on Climate-smart cocoa by re-engaging both public and private sector companies; 3) Develop a framework to institutionalize a stepwise investment approach for cocoa extension delivery and voluntary standard programs under certification. This infographic highlights the lows and the highs of implementing CSC through the private sector lens and provides insights to others enrolling in this type of endeavor.